PROFIL BADAN USAHA MILIK DESA (BUMDes) â€œRAJAWALIâ€ DI DESA TOLOMBUKAN KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA (Profile of Village Owned Business Agency (Bumdes) "Rajawali" In Tolombukan Village, Pasan Sub District, Southeast Minahasa Regency) - Sidistra Paskaforets Gahung; Lyndon R. J. Pangemanan; Grace A. J. Rumagit (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to examine the profile of RAJAWALI village-owned enterprises (BUMDes) in Tolombukan Village, Pasan Sub District, Southeast Minahasa Regency. This research was conducted for 1 year from March 2019 - November 2020. The data used in this study are primary data and secondary data. Primary data collection through interviews and filling out a questionnaire with 20 questions that have been compiled and directly to the 20 research respondents. Secondary data were obtained from related agencies, namely the village office, the BUMDes secretariat, the internet, books and journal articles. The data analysis carried out in this research is descriptive analysis in tabular form and described. The research results showed that the profile of the Village Mulik Business Entity (BUMDes) Rajawali which includes the type of business, management management, capital used, labor employed, and profit levels are in accordance with AD / ART, the presence of BUMDes in the community of Tolumbukan Village is a forum for economic improvement community and being able to empower the community and be able to create jobs, this is evidenced by the community being involved in every existing business unit.